2020
DOI: 10.1186/s43094-020-00051-z
|View full text |Cite
|
Sign up to set email alerts
|

Zotepine loaded lipid nanoparticles for oral delivery: development, characterization, and in vivo pharmacokinetic studies

Abstract: Background The purpose of this work was to prepare and evaluate the zotepine (ZT) loaded solid lipid nanoparticles (SLNs) that might improve the oral bioavailability. ZT is an anti-psychotic drug used for the treatment of schizophrenia. Currently, it is available as parenteral and oral dosage form. But, ZT has a poor oral bioavailability of about 7–13% due to limited aqueous solubility and first-pass effect. ZT-SLNs were developed using homogenization method and characterized for optimal system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Ex-vivo permeability across the rat intestine revealed a significant enhancement in drug permeability when compared with drug suspension. 40 Likewise, Soni et al found that the prepared lipid nanoparticles that consisted of SA as lipid phase and T-80, capryol 90, and labrasol as surfactants were able to enhance the permeability of Pemetrexed. Ex-vivo permeability study revealed that the developed formulation enhanced the drug permeability ratio by about 6-folds compared to the drug solution.…”
Section: Discussionmentioning
confidence: 99%
“…Ex-vivo permeability across the rat intestine revealed a significant enhancement in drug permeability when compared with drug suspension. 40 Likewise, Soni et al found that the prepared lipid nanoparticles that consisted of SA as lipid phase and T-80, capryol 90, and labrasol as surfactants were able to enhance the permeability of Pemetrexed. Ex-vivo permeability study revealed that the developed formulation enhanced the drug permeability ratio by about 6-folds compared to the drug solution.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the oral bioavailability of zotepine, Nagaraj, et al created Zotepine loaded lipid nanoparticles (ZT-SLN) for oral administration. By freezing the optimised ZT-SLN formulation at or below 80 °C for an extended period of time and lyophilizing it under applied vacuum, the author lyophilized the formulation (Nagaraj et al, 2020).…”
Section: Lyophilizationmentioning
confidence: 99%
“…The Higuchi model for the release kinetics states that the rate of the release of the drug is a function of the square root of the time [ 41 , 64 ]. Lastly, Korsmeyer–Peppas is a semi-empirical model that can usually be used to describe the mechanism of the drug release phenomenon consisting of diffusion or swelling [ 41 , 65 ].…”
Section: Resultsmentioning
confidence: 99%